Computer Aided Assessment of Contaminant Transport in Landfill - Loh, Eric Wooi Kee; Deprizon, Syamsunur; Md. Munir, Hayet Khan*; Deepak, Tirumishi Jada* (Print and online quarterly, 2017)
Migration of contaminants from a landfill poses considerable attention to environmental scrutiny. Some experience practitioner has made calculated guesses in the contaminant transport through varies material. This paper presents the use of software modelling as a tool to study the sensitivity of the pollutant leachate movement with response to the shallow but complex site geology. The geometry, contaminant transport parameter as well as the properties of sub-soil was varied. The resulting dispersion of the leachate in the subsurface was predicted. Sensitivity analysis also suggested that changes in aquifer hydraulic conductivity, landfill geometric and dispersivity have the most significant impact on model output indicating that these parameters should be carefully selected when similar modelling studies are performed.